2020
DOI: 10.2144/fsoa-2019-0074
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Activity of fosfomycin–meropenem and fosfomycin–colistin Against Carbapenem Resistant Klebsiella Pneumoniae : an In Vitro Evidence

Abstract: Aim: To evaluate the antibacterial activity of fosfomycin–meropenem and fosfomycin–colistin combinations against carbapenem-resistant Klebsiella pneumoniae (CR-Kp). Methods: A total of 50 CR-Kp isolates recovered from blood cultures were included in this study. All the CR-Kp isolates were screened for the presence of carbapenem resistant genes blaIMP. blaVIM. blaNDM. blaOXA-48 like, blaKPC. blaGES.#x00A0;and blaSPM. Combination testing of fosfomycin–meropenem and fosfomycin–colistin were performed using time-k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 28 publications
(27 reference statements)
6
11
0
Order By: Relevance
“…The same effects of FOS/COL (Yu et al 2018;Ku et al 2019;Bakthavatchalam et al 2020) and COL/NIT (Pogue et al 2011;Corvec et al 2013;Ceccarelli et al 2015) were also reported against other Gram-negative bacteria. This suggests a wide-spectrum of activity of COL combinations with FOS and NIT against different Gram-negative pathogens.…”
Section: Time-kill Kineticssupporting
confidence: 72%
“…The same effects of FOS/COL (Yu et al 2018;Ku et al 2019;Bakthavatchalam et al 2020) and COL/NIT (Pogue et al 2011;Corvec et al 2013;Ceccarelli et al 2015) were also reported against other Gram-negative bacteria. This suggests a wide-spectrum of activity of COL combinations with FOS and NIT against different Gram-negative pathogens.…”
Section: Time-kill Kineticssupporting
confidence: 72%
“…Three of the patients who achieved bacterial eradication were being treated for VAP with septic shock and received fosfomycin in combination with colistin. Thus, our results are similar to prior studies which suggest the efficacy of fosfomycin in combination with other antimicrobial agents, particularly colistin, can be improved [ 5 8 20 26 28 ]. In fact, synergy found with fosfomycin combination therapy may result in reducing the fosfomycin MIC against CRE isolates [ 10 28 ].…”
Section: Discussionsupporting
confidence: 91%
“…Thus, our results are similar to prior studies which suggest the efficacy of fosfomycin in combination with other antimicrobial agents, particularly colistin, can be improved [5,8,20,[26][27][28]. In fact, synergy found with fosfomycin combination therapy may result in reducing the fosfomycin MIC against CRE isolates [10,28].…”
Section: Fosfomycin Dosing For Cre Infectionsupporting
confidence: 90%
“…TKA not only confirmed but demonstrated even higher synergy against the representative XDR NDM K. pneumoniae isolate. Bactericidal activity was observed as early as 6 h of incubation with 0.25 MIC fosfomycin (16 mg/L) and 1/32 MEM MIC (2 mg/L) which persisted for 24 h. Synergy levels achieved in OXA-232/48 producing Klebsiella pneumoniae in our study was 94% while other studies reported 20–42% synergy [ 21 , 22 ]. Samonis et al reported over 70% synergy in KPC producing Klebsiella pneumoniae [ 23 ].…”
Section: Discussionsupporting
confidence: 44%